The last of the Mohicans - Cooper, James Fenimore, 1789-1851 (Penguin classics., 1986)
Chingachgook and Uncas are the last living members of the great Mohican tribe. Hawkeye, a colonial scout, is their companion and loyal friend. In the midst of the French and Indian War, the three take great risks to lead the two daughters of a British colonel to safety through the battle-torn northern wilderness. When the girls are captured by the vicious Huron tribe, Chingachgook, Uncas, and Hawkeye risk their very lives to rescue them.